Integrative chloroplast omics in citrus: computational insights into genomic structural adaptation and phylogenetic relationships from 35 species - Lin, Su; Shu, Jinfang; Kang, Chengnan; Fang, Wenxin; Liang, Xingxing; Xu, Kai; Ma, Haijie (Frontiers in Plant Science, 2026)
The chloroplast genome serves as a valuable tool for plant phylogenetic studies due to its conserved structure and slow evolutionary rate. Despite the economic importance of the genus Citrus, comprehensive comparative analyses of chloroplast genomes across multiple species remain limited. As one of the ancestors of Citrus, Citrus medica L. serves as a key representative in studies of the origin and evolution of the genus. In this study, we conducted a comprehensive comparative analysis of chloroplast genomes from 35 Citrus species and their close relatives, with C. medica as a focal species, to investigate structural variation, codon usage patterns, and phylogenetic relationships. All genomes exhibited a typical quadripartite structure, ranging from 159 to 161 kb with GC contents of 38.41-38.49%. While genome synteny was highly conserved, expansions and contractions at IR boundaries provided species-specific variation. SSR analysis revealed abundant mononucleotide repeats with a strong AT bias, predominantly distributed in non-coding regions. Codon usage analysis indicated a preference for A/U-ending codons, and ENC-GC3s, neutrality plot, and PR2 analyses suggested that natural selection was the main force shaping codon usage bias. Most protein-coding genes were under strong purifying selection, whereas matK and rps16 exhibited elevated Ka/Ks ratios, suggesting relaxed selective constraints or potential signals of positive selection. Phylogenomic analysis strongly supported the monophyly of Citrus and resolved intrageneric relationships, grouping species into distinct ancestral and cultivated clades. Overall, this study provides essential chloroplast genomic resources for molecular breeding, species identification, and understanding Citrus adaptation.